“Evaluación de cuatro especies forestales en rendimiento de celulosa para la fabricación de papel” - Flores Flores, José (2001)
The wood samples of four (4) forestal especies were studied with regard to chemical composition on basic structure, using chemical proceedments and according to ASTM technical standards. The essays were realized by each species starting dried sawdust samples through oven ( anhydrous dry) preceding an extraction wi th neutral sol vents of components denominated extractibles. Average resul ts were obtained on four ( 4) species wi th three (3) repetitions ea ch it, su ch as cellulose, holocellulose, lignin and ashes. Obtained values on four (4) species are compared to thenselves as well as other species whose wood get industrially pulp. There were signif icant differences with regard to cellulose contents on four ( 4) studied species, recording high values (56.7%) to the species Cupania cineria, comparing the rest species (Acalypha macrostachya, Cecropia polystachya, and Ochroma pyramidale) For complementing this study realized essays with test -tubes 10x3x3 cm., on. four (4) species with objective to determine the basic and anhydrous density, getting basic density values starting 0.143 gr/ cm3 (Ochroma pyramidale) up to 0.592 gr/ cm3 (Cupania cineria) The obtained results as to their structure chemical composition, will allow us to know fibrous potential on st udied species and gi ve to them a maj or use su ch as in paper industry. The paper did show extractive porcentual values from 12 to 2.6% alcohol and 3.0 to 2.9% distilled water, cellulose (44.4 56.7%), lignin (8.2 10.10%), ashes (0.9 1.20%) and b as i c den s i t y ( O • 1 4 3 - O • 5 9 2 gr/ cm3) ranks that are in si de of values realized by other research workers specialized on latifoliated woods.